2006
DOI: 10.1177/1367493506066480
|View full text |Cite
|
Sign up to set email alerts
|

Caring for children with learning disabilities who present problem behaviours: a maternal perspective

Abstract: The theoretical cognitive model of stress and coping provides a structure to obtain and analyse maternal perceptions of caring for children with learning disabilities who present severe problem behaviours. The Family Fund database identified 18 families who met the sample criteria of children aged five years to 15 years with severe to moderate learning disability presenting severe problem behaviour. Physical aggression was reported to be the primary behavioural problem for 13 of the children. Interviews undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 15 publications
1
50
0
Order By: Relevance
“…Results showed that the participants tended to experience greater difficulty with practical and social care tasks despite managing problem behaviours featuring within the theme of impact upon the family (Johnson et al, 2006). They also expressed a lack of satisfaction with formal support and low service provision.…”
Section: Howie-davies and Mckenziementioning
confidence: 79%
See 2 more Smart Citations
“…Results showed that the participants tended to experience greater difficulty with practical and social care tasks despite managing problem behaviours featuring within the theme of impact upon the family (Johnson et al, 2006). They also expressed a lack of satisfaction with formal support and low service provision.…”
Section: Howie-davies and Mckenziementioning
confidence: 79%
“…Tiredness and a lack of childcare also contributed to social isolation (Todd and Jones, 2005) as well as the amount of planning and routine that is involved in every activity, meaning that the child's disability dominated most activities (Johnson et al, 2006;Todd and Jones, 2005). Parents in the study by Catherall and Iphofen (2006) expressed feelings of frustration that the amount of planning and structure that has to go into each activity meant that the family spontaneity was affected.…”
Section: Impact Upon the Familymentioning
confidence: 92%
See 1 more Smart Citation
“…Researchers have also identified several negative sequelae in parents of children with learning disabilities (Al-Yagon 2007;Johnson et al 2006). Specifically, parents of children with learning disabilities report significantly more symptoms of depression and poor parent coping strategies (Al-Yagon 2007).…”
mentioning
confidence: 97%
“…Parents who are asked to implement strategies that outsource them will experience greater level of secondary stress (Johnson, O"Reilly & Vostanis, 2006). It is vital to advise parents of special need child to be pragmatic when deploying their resources lest the cohesiveness of family be jeopardized.…”
Section: Empowering Approachesmentioning
confidence: 99%